A technique for removal of forearm dynamic compression plate with stripped screws: a report of three cases - Lee, C.K.; Kwan, M.K.; Chua, Y.P. (2009)
Removal of plates is a procedure commonly performed by orthopaedic surgeons and stripped screws are probably the most common problem encountered during this procedure. Stripped screws are caused by slippage between the screwdriver and the screw. Due to the inherent difficulty in removing such screws, surgeons should be knowledgeable in techniques for their removal and should be equipped with the proper instruments to expedite the procedure. There are few published articles about such techniques. This report describes a technique for removal of plates with stripped screws. The tip of a stripped screw is approached from the far cortex and then reamed with a trephine reamer in the direction of the screw until both cortices are cleared. The plate is then removed with stripped screws attached. All the removals utilizing this technique to date have been successful with no complications, and this method is safe, efficient and technically easy to learn.